ANALISIS EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL PAJAK BAHAN BAKAR KENDARAAN BERMOTOR DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH PROVINSI SULAWESI UTARA - Rajagukguk, Tondy Maranatha; Tinangon, Jantje J.; Wokas, Heince R. N. (JURNAL RISET AKUNTANSI GOING CONCERN, 2019)
Vehicle fuel tax is a type of local tax, which is a source of revenue to increases locally-generated revenues. Vehicle fuel tax is managed by Regional Tax and Retribution Management Agency (RTRMA) of North Sulawesi, where each registered companies are compulsory levy, which is periodically required to report and deposit the proceeds of the sale of fuel to RTRMA. This research aims to know the effectiveness of the internal control system and the contribution of vehicle fuel tax to the locally-generated revenue of North Sulawesi. The method used in this research is descriptive qualitative. The results of the research show that the internal control system in the calculation process, collection and reporting of vehicle fuel tax has been worked well. In addition, the criteria for effectiveness and contribution based on the calculation of the average vehicle fuel tax revenue in 2013-2017, explained that the results of vehicle fuel tax were very effective and sufficiently contributed to the locally-generated revenue of North Sulawesi.Keywords: Internal Control System, Vehicle Fuel Tax